Effect of Three Types of Organic Manures on the Grain Yield of Wheat in Khashm Elgirba Soil Series, Sudan - I. Adam, Adam; A. Ali, Zaheeruddin (المجلة الزراعية; مجلد 2 عدد 2 (2004), 2021)
This study was conducted during seasons 1998/1999 and 1999/2000 at a farm adjacent to New Halfa town to assess the effect of farm yard manure (FYM), filtermud (FM) and bagasse (B) on yield of wheat. Each manure was applied to soil surface at a rate of    0, 15, 30, 45, 60 and 75 t ha -1 in a randomized complete block design (RCBD) with four  replications. Each manure was incorporated into the soil using hand tools. The results of nitrogen (N) and phosphorus (P) uptake (kg ha -l ( revealed that wheat plants withdrew higher amounts of N from the soil treated with FYM as compared to those treated with either FM of B. The amounts of P withdrawn by the wheat plants from the soil treated by the three sources of organic manures at all levels of application were very low and ranged from 1.85 to 6.67 kg P ha -l. The present study also showed that increasing rates of application of each of the tested manures resulted in highly significant increases in grain yield. These organic manures can be ranked according to their effectiveness in increasing the yield of wheat as follows: FYM > FM>B. The economic evaluation of the study indicated that only the lowest level of application (15 t ha -l ) of FYM and FM gave positive net benefits albeit lower than those reported for the control. However, net losses from the higher rates of application of each of F YM and FM and of all rates of the B were obtained. This was presumably due to high cost of both transportation and application of these bulky organic manures.